2019
DOI: 10.1111/epi.16328
|View full text |Cite
|
Sign up to set email alerts
|

A somatic mutation in MEN1 gene detected in periventricular nodular heterotopia tissue obtained from depth electrodes

Abstract: Periventricular nodular heterotopia (PNH) is a common structural malformation of cortical development. Mutations in the filamin A gene are frequent in familial cases with X‐linked PNH. However, many cases with sporadic PNH remain genetically unexplained. Although medically refractory epilepsy often brings attention to the underlying PNH, patients are often not candidates for surgical resection. This limits access to neuronal tissue harboring causal mutations. We evaluated a patient with PNH and medically refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The timing of mutation is often associated with the severity of phenotype ( Sarnat, 1987 ; Sarnat and Flores-Sarnat, 2014 ). In this context, somatic mutations have recently been found to exert and important contribution to MCDs with focal insult, such as in focal heterotopia, focal cortical dysplasia and hemimegalencephaly ( Jamuar et al, 2014 ; Jansen et al, 2015 ; Gonzalez-Moron et al, 2017 ; Montier et al, 2019 ). Somatic mutations can be of type 1 or type 2, which cause a new heterozygous mutation or lead to a loss of heterozygosity, respectively ( Qin et al, 2010 ; Jansen et al, 2015 ; Juric-Sekhar and Hevner, 2019 ).…”
Section: Malformations Of Cortical Developmentmentioning
confidence: 99%
“…The timing of mutation is often associated with the severity of phenotype ( Sarnat, 1987 ; Sarnat and Flores-Sarnat, 2014 ). In this context, somatic mutations have recently been found to exert and important contribution to MCDs with focal insult, such as in focal heterotopia, focal cortical dysplasia and hemimegalencephaly ( Jamuar et al, 2014 ; Jansen et al, 2015 ; Gonzalez-Moron et al, 2017 ; Montier et al, 2019 ). Somatic mutations can be of type 1 or type 2, which cause a new heterozygous mutation or lead to a loss of heterozygosity, respectively ( Qin et al, 2010 ; Jansen et al, 2015 ; Juric-Sekhar and Hevner, 2019 ).…”
Section: Malformations Of Cortical Developmentmentioning
confidence: 99%
“…Rarely, agyria/pachygria and SBH can be identified in the same patient. In a large lissencephaly study genetic analysis revealed a causal mutation in 123/155 SBH cases, the majority of which were DCX mutations, and several LIS1 mutations (34). So in total, only 2 genes explained 80% of cases (34).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In a large lissencephaly study genetic analysis revealed a causal mutation in 123/155 SBH cases, the majority of which were DCX mutations, and several LIS1 mutations (34). So in total, only 2 genes explained 80% of cases (34). DCX mutations in females cause a thick or thin SBH, with either a diffuse localization or anterior to posterior gradient (Figure 2B) (5).Recently, a novel lissencephaly gene, CEP85L has been discovered, mutations cause a posterior predominant agyria/pachygyria or SBH (35,36).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations